Diffusion of innovation: customer relationship management adoption in supply chain organizations - Vicky Ching Gu; Marc J. Schniederjans; Qing Cao (International Journal of Quality Innovation, 2015)
The successful diffusion of innovations in rapidly changing supply chain technological environments is essential to support operations and supply chain management functions. In this paper we conceptualize and develop a framework for research into the diffusion of innovations in organizations pertaining to software adoption in supply chain management. Incorporating Task-Technology Fit theory with a network externalities model, we develop a novel approach in customer relations management (CRM) software adoption. An empirical study using Partial Least Squares (PLS) on data from US supply chain managers is utilized to confirm the usability of the proposed framework as well as confirming the efficacy of the proposed combined methodological approach suggested in this paper. The results also show the direct and indirect network externalities of system quality, ease of use, system reliability, and authority can moderate the CRM adoption relationship in organizations, suggesting the possibility that other moderating network externality variables may impact CRM adoption.
Keywords: 650; Innovation diffusion; Customer relations management; System quality; Software adoption